Organ Donation: Behaviour and Beliefs in Sweden - Theres Södereld MSc; Åsa Engström PhD; Katarina Lindgren MSc; Angelica Forsberg PhD (SAGE Publishing, 2024)
Introduction Barely one-fifth of people in Sweden have expressed their will regarding organ donation in the national Swedish Donor Registry, and the number of organ donations in Sweden remains low. Objective The aim of this study was to map behaviour and beliefs regarding organ donation in Sweden. Methods In a descriptive cross-sectional survey following a quantitative approach and 600 questionnaires were issued to randomly selected individuals across Sweden. Of them, 206 (36.3%) were completed. Data were analysed using descriptive statistics and presented as frequencies and percentages. Analytical statistical testing involved Pearson chi-square tests, Mann-Whitney U tests, and Kruskal-Wallis tests. Results The results indicate a discrepancy between positive opinion about organ donation in Sweden and the number of people enrolled in the Swedish Donation Registry. The most common argument for not wanting to donate organs was the notion of being too old to. Although self-rated knowledge about organ donation was admittedly low, so was interest in interest in learning more about it. Younger patients more frequently wanted information than older patients did. Conclusion Not wanting to donate organs due to age and/or illness may indicate a misconception. Making one's will known does not involve assessing one's health status or age but solely concerns the wish to do so. The findings thus raise an important question: How can people's interest in learning more about organ donation be induced in ethical ways?